The Effect of Work Culture and Work-Life Balance on Employee Productivity in Manufacturing Area - Triastutik, Ananda Hesti; Ningrum, Ika Putri Aisya (Lentera Ilmu Nusantara, 2025)
The research reviewed as a whole explores key themes in organizational and employee dynamics, with a focus on Industry 4.0, work-life balance, work culture, and sustainability. Key findings highlight the role of continuous vocational training, safe workplace practices, and HR strategies in improving productivity, well-being, and innovation. In addition, digital transformation, work culture, and manufacturing advancements are analyzed as important factors that affect employee satisfaction and retention, operational efficiency, and sustainable growth across various industries. This study was conducted with a total sample of 75 respondents. The results indicate that, partially, work culture has a significant influence on employee productivity, whereas work-life balance does not have a measurable impact. These findings suggest that fostering a strong and supportive work culture is crucial for enhancing employee performance, while work-life balance alone may not directly contribute to productivity in the manufacturing sector. The implications of this research highlight the need for organizations to prioritize cultural development initiatives, leadership engagement, and workplace policies that reinforce a high-performance work environment.